Building content literacy : strategies for the adolescent learner - Sejnost, Roberta. 4 0 16; Thiese, Sharon; 5 (Thousand Oaks, CA : Corwin, 2010)
Offers a series of strategies for middle and high school teachers to help develop reading, writing, and critical thinking skills across the curriculum, with reproducible worksheets and examples.
The challenge of adolescent literacy -- Teaching specialized and technical vocabulary -- Reading to learn in content area disciplines -- Writing to learn in content area disciplines -- Speaking to learn in content area disciplines -- Fostering real world literacy.
Includes bibliographical references (p. 150-157) and index.
Professional;Professional.
Keywords: 2 -- 0; 6; Correlation with content subjects. -- Language arts (Secondary);Language arts -- 20; 20; 2